2014
DOI: 10.1016/j.rmed.2013.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a COPD population categorised using the GOLD framework by health status and exacerbations

Abstract: GOLD proposed a COPD assessment framework focussed on symptoms measured by the COPD Assessment Test™ (CAT) or the mMRC and on exacerbation risk based on poor lung function (FEV1 <50%) or a history of ≥2 exacerbations in the previous year. This analysis examined the characteristics of COPD patients recruited from routine clinical settings and classified using the GOLD framework. 1041 European COPD patients (38.5% from primary care) from the Adelphi Respiratory Disease Specific Programme with information on CAT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 23 publications
4
40
1
4
Order By: Relevance
“…In the new classification, the shift of patients towards category D with a high risk in comparison to not numerous grade IV from the previous classification is caused by recurrent exacerbations (≥ 2/year) in a significant proportion of respondents (in this way 80% patients were classified to groups D or C). But in the two quoted studies there is a higher proportion of patients from groups B or D in relation to the present study, which results from more severe symptoms (in the present study A+C/B+D -69%/31% vs. Johannessen [13] 26%/74% vs. Jones [14] 10%/90% for CAT and 51%/49% for mMRC). It is possible that the differences also result from the intensity of treatment; the quoted studies do not contain data about the used therapy.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In the new classification, the shift of patients towards category D with a high risk in comparison to not numerous grade IV from the previous classification is caused by recurrent exacerbations (≥ 2/year) in a significant proportion of respondents (in this way 80% patients were classified to groups D or C). But in the two quoted studies there is a higher proportion of patients from groups B or D in relation to the present study, which results from more severe symptoms (in the present study A+C/B+D -69%/31% vs. Johannessen [13] 26%/74% vs. Jones [14] 10%/90% for CAT and 51%/49% for mMRC). It is possible that the differences also result from the intensity of treatment; the quoted studies do not contain data about the used therapy.…”
Section: Discussioncontrasting
confidence: 73%
“…The limitation of the cohort was the fact that it recruited patients with FEV 1 below 80% of predicted value, so it excluded patients with a mild degree of obturation, which made the proportion of patients in groups A and B smaller, and consequently made the proportion of patients in groups C and D bigger. Jones et al [14] also classified patients according to the 2011 GOLD. The cohort from the Adelphi Respiratory Disease Specific Programme, similarly as in the previous study, consisted of approximately 1000 patients recruited during routine visits (38.5% primary care clinic).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the GOLD 2011 re-classification shifted the overall COPD severity distribution to more severe categories, but without clearly documented benefits on outcomes [14]. Furthermore, the ABCD classification based on airflow severity and patient-reported outcome caused some confusion: for example, group C (high risk without significant symptoms) was rather uncommon, and had similar exacerbation frequency than group B (high symptoms but low risk); on the other hand, group D (which included subjects with severe airflow limitation alone, or with history of frequent exacerbations alone, or with both risk factors) had significant heterogeneity in exacerbation rate [15,16].…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…Data from different COPD cohorts have been used to understand the percentage of patients falling into groups A, B, C, and D; these data are shown in table 1 9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] . There are considerable differences between some studies, which can be attributed to many factors, including the study design and inclusion criteria, how the patients were recruited (e.g.…”
Section: The Combined Assessment Explainedmentioning
confidence: 99%
“…GOLD C comprised 13%, reflecting a general trend for this category to be a minority of the population. It should be noted that studies comparing the use of CAT and mMRC have generally shown an increase in severity towards more GOLD B and D patients using CAT 11,16,20,21 , indicating that these tools do not provide equivalent results.…”
Section: The Combined Assessment Explainedmentioning
confidence: 99%